1-b2 x( умножить) (1/(b-1)2 - 1/1-b2)+2b/1+b при b=-0,2

1-b2 x( умножить) (1/(b-1)2 - 1/1-b2)+2b/1+b при b=-0,2
Гость
Ответ(ы) на вопрос:
Гость
(1-b²)(1/(b-1)² -1/(1-b²)) +2b/(1+b), при b= -0.2 1 -b² = -(b² -1) = -(b -1)(b +1), (b-1)² =(1-b)² (b+1)(b-1)² это общий знаменатель 1) в скобках ((b+1)+(b-1)) /(b+1)(b-1)² =(b+1+b-1) /(b+1)(b-1)² =2b /(b+1)(b-1)² 2) умножение (1 -b²)*2b /(b+1)(b-1)² =(1-b)(1+b)*2b /(b+1)(1-b)² =2b/(1-b) 3) сложение 2b/(1-b) +2b/(1+b) =(2b(1+b) +2b(1-b)) /(1-b)(1+b) =(2b+2b²+2b-2b²)/(1-b)(1+b) =4b/(1-b)(1+b) 4) подставим значение 4*(-0.2) /(1-(-0.2))(1+(-0.2) = -0.8 /(1.2*0.8) = -1 /1.2 = -1 : 12/10 = -1 * 10/12 = -10/12 = -5/6 ответ: -5/6(минус пять шестых)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы